Offshoring and firm performance: self-selection, effects on performance, or both? - Joachim Wagner (Institute for the Study of Labor (IZA), 2009)
This paper uses unique new data for German manufacturing enterprises from matched regular surveys and a special purpose survey to investigate the causal effect of relocation of activities to a foreign country on various dimensions of firm performance. Enterprises that relocated activities abroad in the period 2001-03 for the first time are compared to firms that did not relocate activities abroad before 2006. The comparison is performed for both 2004 (to document differences between the two groups of firms after some of them started to relocate abroad) and for 2000 (when none of them did relocate abroad). It turns out that, compared to non-offshoring firms, firms that relocated activities were larger and more productive, and had a higher share of exports in total sales. All these differences existed in 2000, the year before some firms started to relocate, and this points to self-selection of better firms into offshoring. This finding is in line with results from recent theoretical models and with results from other countries. To investigate the causal effects of relocation across borders on firm performance, six different variants of a matching approach of firms that did and did not start to relocate abroad in 2001-03 were performed based on a propensity score estimated using firm characteristics in 2000 and the change in the performance variable between 1997 and 2000. The performance of both groups was compared for 2004-06 when some firms were relocating firms and the others were not. Broadly in line with hypotheses derived from the literature there is no evidence that offshoring has a negative causal impact on employment in offshoring firms. The effect is positive and large for productivity, and weak evidence for a positive effect on the wage per employee, the proxy variable for human capital intensity used, is found. Contrary to what is often argued, therefore, we find no evidence for a negative causal effect of offshoring on employment in Germany or on other core dimensions of firm performance.
Keywords: F23; 330; Offshoring; Germany; enterprise panel data; Offshoring; Auslandsproduktion; Unternehmensentwicklung; Produktivität; Beschäftigungseffekt; Panel; Schätzung; Deutschland